Features of hydrogen adsorption on a Ni(997) surface - Karner, H.; Luger, M.; Steinrück, Hans-Peter; Winkler, A.; Rendulic, K.D. (Surface Science, 1985)
The change of the initial sticking coefficient for a Maxwellian beam of hydrogen on Ni(997) has been determined as a function of beam temperature and angle of incidence. At low temperatures adsorption is governed by the steps, at high temperatures adsorption on the terraces is more dominant. Adsorption on the terraces is probably an activated process whereas adsorption on the step sites is non-activated. There seems to be little diffusion of undissociated H between steps and terraces. © 1985.